2001
DOI: 10.1002/yea.776
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae cell wall chitin, the Kluyveromyces lactis zymocin receptor

Abstract: The exozymocin secreted by Kluyveromyces lactis causes sensitive yeast cells, including Saccharomyces cerevisiae, to arrest growth in the G 1 phase of the cell cycle. Despite its heterotrimeric (abc) structure, intracellular expression of its smallest subunit, the c-toxin, is alone responsible for the G 1 arrest. The a subunit, however, has a chitinase activity that is essential for holozymocin action from the cell exterior. Here we show that sensitive yeast cells can be rescued from zymocin treatment by exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
99
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 66 publications
4
99
0
Order By: Relevance
“…Consistent with an impact on early events, class I mutations in KTI2/CHS3 and KTI10/ PMA1 protect solely against exozymocin and affect chitin synthesis and plasma membrane H ϩ -ATPase function, respectively (11,33,43). In line with this, holozymocin binds chitin in vitro and has exochitinase activity (10,33).…”
mentioning
confidence: 55%
See 3 more Smart Citations
“…Consistent with an impact on early events, class I mutations in KTI2/CHS3 and KTI10/ PMA1 protect solely against exozymocin and affect chitin synthesis and plasma membrane H ϩ -ATPase function, respectively (11,33,43). In line with this, holozymocin binds chitin in vitro and has exochitinase activity (10,33).…”
mentioning
confidence: 55%
“…Consistent with an impact on early events, class I mutations in KTI2/CHS3 and KTI10/ PMA1 protect solely against exozymocin and affect chitin synthesis and plasma membrane H ϩ -ATPase function, respectively (11,33,43). In line with this, holozymocin binds chitin in vitro and has exochitinase activity (10,33). As judged from the finding that hygromycin B, whose antibiotic action requires an intact membrane potential established by H ϩ -ATPase Pma1/ Kti10, is inert against kti10 cells, plasma membrane energization is likely to be required for zymocin action (43,50).…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…In the search for novel and more selective antifungal agents, fungal cell wall components represent primary targets, as these structures are restricted to yeasts and higher fungi and do not occur in human cells [44,45]. Each of the mentioned cell wall components has been shown to act as the primary binding site for different yeast killer toxins [46][47][48][49]. In addition, for killer toxins secreted by various strains of the yeast Hansenula it was demonstrated that these toxins not only bind to yeast cell wall components, but that they also strongly inhibit de novo L-1,3-D-glucan biosynthesis [50,51].…”
Section: Mycoviruses and Toxinsmentioning
confidence: 99%